A comparison of plant communities in restored, old field, and remnant coastal prairies. Issue 3 (9th March 2021) - Feher, Laura C.; Allain, Larry K.; Osland, Michael J.; Pigott, Elisabeth; Reid, Christopher; Latiolais, Nicholas
Abstract : Temperate grasslands are experiencing worldwide declines due to habitat conversion. Grassland restoration efforts are employed to compensate for these losses. However, there is a need to better understand the ecological effects of grassland restoration and management practices. We investigated the effects of three different grassland management regimes on plant communities of coastal prairie ecosystems in southwest Louisiana (the United States). We compared old fields, prairie remnants, and restored prairies. Coastal prairies are a unique type of grassland historically present across southeast Texas and southwest Louisiana. Old fields represent former coastal prairie habitats allowed to revegetate naturally without active management. Remnant coastal prairies are small, isolated patches of comparatively intact prairie. Restored coastal prairies have been actively restored by planting native coastal prairie vegetation and managed with prescribed burning, mowing, and/or removal of invasive non‐native species. Our work was conducted in three old fields, four remnants, and four restored prairies. Old fields were dominated by non‐native species with low conservation value, whereas remnant prairies were dominated by native species with high conservation value. Remnants had a mean species richness of 75 species per site, which is higher than most other tallgrass prairie ecosystems in North America. Restored sites were dominated by native species with high conservation value, although the composition differed between restored and remnant sites. Collectively, our results: (1) reinforce the importance of identifying and preserving remnant coastal prairies; and (2) show that restoration of degraded coastal prairies is a viable strategy for supporting the persistence of these unique grassland ecosystems.